Chemical desiccation tolerance and nonstructural carbohydrate dynamics in winter wheat - Mulat, Teshome Girma, author; Haley, Scott, advisor; Brick, Mark A., committee member; Byrne, Patrick F., committee member; Stushnoff, Cecil, committee member (Colorado State University. Libraries, 2004)
Winter wheat (Triticum aestivum L.) often experiences postanthesis drought stress that causes crop yield and quality losses. Contact chemical desiccants have been proposed as a means of identifying genotypes with improved ability to support grain filling from stem nonstructural carbohydrates (NSC) in the absence of photosynthesis during grain filling. Information on genetic variation in stem NSC, and its remobilization to developing grains under chemical desiccation, is therefore important. The objectives of this study were (1) to characterize chemical desiccation response, dryland yield performance and NSC concentration and remobilization of F2-derived lines and their parents, (2) determine associations among chemical desiccation injury, dryland performance and NSC measurements, and (3) estimate genotypic variance components of agronomic traits and NSC measurements under chemical desiccation. F2: 4 lines developed from six crosses between seven parents with contrasting agronomic traits were planted in a split plot with two replications in 1998 and 1999 under irrigation at Fort Collins. Sodium chlorate (NaCIO3, 2% W:V, 125 mL m-2) was applied to each subplot 15 d postanthesis. The same lines were also evaluated at four dryland locations (Akron in 1998 and Burlington, Akron, and Walsh in 1999) in a randomized complete block design with two replications. Yield injury from chemical desiccation ranged from 13 to 37% among entries, with reductions in both kernel weight (13 to 23%) and kernel number (8 to 32%). Significant associations were observed between grain yield injury and both biomass injury (r = 0.65, P<0.05) and control kernel weight (r = 0.57, P<0.05). Average performance under dryland conditions was less than that observed under chemical desiccation, although test weight was much less in the desiccated treatment compared to the dryland treatment. Grain yield under dryland conditions was not associated with either grain yield injury or kernel weight injury under chemical desiccation. Significant genotypic variance was observed for most traits examined, suggesting that progress in selection may be realized within these populations. Inconsistency among entries for desiccation tolerance, and the lack of correlation between desiccation tolerance and dryland performance, suggest that additional research is necessary to identify strategies and techniques to successfully exploit the chemical desiccation method for applied wheat breeding programs. Nonstructural carbohydrate concentration was determined from stem samplings made at 14 d postanthesis and at maturity in both the control and desiccated subplots. Significant variation among entries was observed for NSC concentration at postanthesis and maturity in both control and desiccated treatments. Very little consistency among entries was observed for NSC measurements across years. Stem NSC concentration at maturity was lower under desiccation than in the control treatment, suggesting that chemical desiccation reduced the source of NSC. Stem NSC concentration at postanthesis was positively correlated with NSC remobilization during grain filling in the desiccated (r=0.90, P<0.001) treatment, suggesting that the size of the NSC pool available at the onset at grain filling is important for reserve remobilization. Most correlations among grain yield and yield components, and variables related to stem NSC were not significant. Genetic variance estimates indicated that significant genetic variation for NSC concentration and remobilization was present among the lines tested. Selection within populations that have high genetic variance should provide progress to improve NSC parameters.
Keywords: agronomy; plant propagation; agricultural chemicals